Cutaneous and Subcutaneous Soft Tissue Tumours in Snakes: A Retrospective Study of 33 Cases. Issue 1 (July 2016) - Dietz, J.; Heckers, K.O.; Aupperle, H.; Pees, M.
Summary: Cutaneous and subcutaneous soft tissue tumours have been rarely described in detail in snakes. Several malignant entities show strikingly similar histological patterns and therefore the term soft tissue sarcoma (STS) has become a standard histopathological diagnosis. The present study characterizes soft tissue tumours in 33 snakes. Samples included 29 surgically excised masses and four carcasses. Additionally, six animals were humanely destroyed and submitted for necropsy examination following tumour recurrence. Benign neoplasms ( n  = 8) were described as lipomas of varying differentiation. Recurrence was observed in two of five snakes in which the clinical course was recorded. Malignant neoplasms ( n  = 25) were diagnosed as STS and graded according to a three-point system previously applied to canine STS. Five (20%) of the primary tumours were classified as grade 1, eleven (44%) as grade 2 and nine (36%) as grade 3 sarcomas. Clinically, recurrence of STS was observed in 11 of 17 cases with available follow-up information. Pathologically, multiple cutaneous metastases were found in one grass snake ( Natrix natrix ), while visceral metastases were observed in one carpet python ( Morelia spilota ) and two corn snakes ( Pantherophis guttatus ). Metastatic risk appears to increase with histological grade. Surgical excision generally represents the current therapy of choice for STS. This study includes the first reports of conventional lipomas in a ribbon snake ( Thamnophis radix ), angiolipomas in a black-headed python ( Aspidites melanocephalus ) and a corn snake as well as of STS in a Jamaican boa ( Epicrates subflavus ), emerald tree boa ( Corallus caninus ), grass snake ( N. natrix ), African house snake ( Lamprophis fuliginosus ), California kingsnake ( Lampropeltis getula californiae ) and common garter snake ( Thamnophis sirtalis ).